ANATOMICAL AND PHYSIOLOGICAL FEATURES OF THE HUMAN CARDIOVASCULAR SYSTEM (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
This article examines the fundamental anatomical aspects of the human cardiovascular system as a single, highly integrated structure that ensures hemodynamics and homeostasis. Particular attention is paid to the macro- and microstructure of the heart (myocardium, conduction system, valve apparatus), as well as the architecture of the vascular bed—the morphological differences between arteries, veins, and the microcirculatory system (capillaries). The paper describes in detail the topography of the systemic and pulmonary circulations, the mechanisms of valve regulation, and the characteristics of collateral blood flow. Understanding the detailed anatomy of the cardiovascular system is the basis for the subsequent study of cardiac pathologies and the improvement of surgical and therapeutic treatment methods. The cardiovascular system is one of the most important systems in the human body, transporting oxygen, nutrients, and hormones, as well as removing waste products. The main components of this system are the heart and blood vessels—arteries, veins, and capillaries. The heart functions as a pump, ensuring the continuous movement of blood through the systemic and pulmonary circulations. This article examines the anatomical features of the heart, the structure of the vascular system, and the functional significance of various parts of the cardiovascular system in maintaining homeostasis.